The escape - Baldacci, David (New York : Hachette Audio, 2014)
John Puller's older brother, Robert, was convicted of treason. His inexplicable escape from prison makes him the most wanted criminal in the country. Some in the government believe that John Puller represents their best chance at capturing Robert alive, and so Puller must bring in his brother to face justice. But Puller quickly discovers that his brother is pursued by others who don't want him to survive. Puller is in turn pushed into an uneasy, fraught partnership with another agent, who may have an agenda of her own.
Compact discs.
Abridged.
Read by Ron McLarty with Orlagh Cassidy.
Keywords: United States. -- Army Criminal Investigation Command -- Fiction; Escaped prisoners -- Fiction; Brothers -- Fiction; Suspense fiction; Mystery fiction